ЖИСМОНИЙ ТАРБИЯ ВА СПОРТ СОҲАСИДА АХЛОҚ МЕЗОНЛАРИ ҲАМДА ИЛМИЙ-ТАДҚИҚОТЛАРНИ РИВОЖЛАНТИРИШ МУАММОЛАРИ - Шопулатов, А.Н. (SCIENCE and SOCIETY, 2022)
This article analyzes the problems of education, as well as the development of scientific research in the field of physical culture and sports, along with this, proposals and recommendations are developed for the correct use of concepts and terms in ensuring continuity in this area, control of work to prevent plagiarism in the preparation of scientific papers.